2020
DOI: 10.1111/cobi.13621
|View full text |Cite
|
Sign up to set email alerts
|

Vascular plant extinction in the continental United States and Canada

Abstract: Extinction rates are expected to increase during the Anthropocene. Current extinction rates of plants and many animals remain unknown. We quantified extinctions among the vascular flora of the continental United States and Canada since European settlement. We compiled data on apparently extinct species by querying plant conservation databases, searching the literature, and vetting the resulting list with botanical experts. Because taxonomic opinion varies widely, we developed an index of taxonomic uncertainty … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 26 publications
0
29
0
2
Order By: Relevance
“…Most species of orchids are threatened in the wild (Cribb et al 2003) and are disappearing from their natural habitats worldwide (Cribb et al 2003;Knapp et al 2020;Wagensommer et al 2020). In Europe, all orchids are terrestrial and can be found in almost all habitats (Hágsater and Dumont 1996;Delforge 2006;Štípková et al 2017).…”
Section: Orchids and Their Specialized Life Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Most species of orchids are threatened in the wild (Cribb et al 2003) and are disappearing from their natural habitats worldwide (Cribb et al 2003;Knapp et al 2020;Wagensommer et al 2020). In Europe, all orchids are terrestrial and can be found in almost all habitats (Hágsater and Dumont 1996;Delforge 2006;Štípková et al 2017).…”
Section: Orchids and Their Specialized Life Strategiesmentioning
confidence: 99%
“…There are many publications on the distribution of orchids worldwide, which indicate that both professionals and the lay public are interested in orchids (e.g. Millar 1978;Seidenfaden and Wood 1992;Bose et al 1999;Dykyjová 2003;Vlčko et al 2003;Jersáková and Kindlmann 2004;Průša 2005;Averyanov et al 2015;Antonopoulos and Tsiftsis 2017;Grulich 2017;Tsiftsis and Antonopoulos 2017;Kühn et al 2019;Knapp et al 2020;Wagensommer et al 2020 and many others). Unfortunately, the family Orchidaceae is one of the most threatened plant families with a high risk of species extinction (Swarts and Dixon 2009).…”
Section: Introductionmentioning
confidence: 99%
“…As the climate changes, botanical gardens play a key role in preserving living collections and seed banks to store and maintain rare plants, for later use in restorations and recovery in the wild (Schulman & Lehvävirta, 2011; Smith et al ., 2019; Knapp et al ., 2021). At an international level, these activities are coordinated by Botanic Gardens Conservation International (http://www.bgci.org).…”
Section: Conservationmentioning
confidence: 99%
“…One of the most important issues of modern conservation biology is to understand temporal changes in the distribution and abundance of various species [1]. During recent decades, the human impact on natural resources and habitats has caused a dramatically large extinction rate and a decline in the number of sites suitable for many plants and animals [2][3][4][5][6][7], with habitat loss and fragmentation being the most important factors [2,3]. Mankind has had a very marked effect on Europe, especially its rapid industrial development in recent centuries, which has resulted in a highly fragmented and degraded landscape [8].…”
Section: Introductionmentioning
confidence: 99%
“…With approximately 28,500 species [21], Orchidaceae is one of the most diverse and widespread families of flowering plant [18]. Unfortunately, most species of orchids are threatened in the wild [22] and are disappearing from their natural habitats worldwide [7,[22][23][24]. In Europe, the main reasons for this dramatic decline are habitat loss, eutrophication and fragmentation [12,23,[25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%